2019
DOI: 10.1186/s12885-019-5622-4
|View full text |Cite
|
Sign up to set email alerts
|

Genomic profiling in ovarian cancer retreated with platinum based chemotherapy presented homologous recombination deficiency and copy number imbalances of CCNE1 and RB1 genes

Abstract: Background Ovarian carcinomas presenting homologous recombination deficiency (HRD), which is observed in about 50% of cases, are more sensitive to platinum and PARP inhibitor therapies. Although platinum resistant disease has a low chance to be responsive to platinum-based chemotherapy, a set of patients is retreated with platinum and some of them are responsive. In this study, we evaluated copy number alterations, HR gene mutations and HR deficiency scores in ovarian cancer patients with prolonge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…The high genomic instability is attributable to the universal presence of TP53 mutations and the frequent alterations in the HR DNA repair pathway ( 23 ). The associations between intrinsic genomic features and platinum sensitivity were explored in-depth with NGS technology in several studies ( 24 , 25 ). However, all those studies derived only single variation, which lacked comprehensiveness and extensiveness.…”
Section: Discussionmentioning
confidence: 99%
“…The high genomic instability is attributable to the universal presence of TP53 mutations and the frequent alterations in the HR DNA repair pathway ( 23 ). The associations between intrinsic genomic features and platinum sensitivity were explored in-depth with NGS technology in several studies ( 24 , 25 ). However, all those studies derived only single variation, which lacked comprehensiveness and extensiveness.…”
Section: Discussionmentioning
confidence: 99%
“…CCNE1 and RB1 are cyclins related to cell cycle transition in the G1-S phase. Tumors with increased CCNE1 copy number are more resistant to platinum therapy, while RB1 loss is associated with high sensitivity to platinum therapy ( 49 , 50 ). Studies have shown that loss of RB1 protein expression is associated with longer OS and PFS ( 47 , 50 , 51 ).…”
Section: Molecular Mechanisms Of Platinum-based Chemotherapy Resistan...mentioning
confidence: 99%
“…4 A). This finding indicated that tumors with CNAs occurring in the SWI/SNF pathway might have DNA repair defects and are sensitive to DNA-damaging therapeutics [ 24 , 25 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%